Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Multifunctional luminogens with synergy of aggregation-induced delayed fluorescence, two-photon absorption and photocurrent generation - Chatterjee, Abhijit; Narayanan, Sundaravalli; Thorat, Sachin; Malik, Ajay J.; Ambhore, Madan D.; Narayanan, Aswini; Sihag, Anil Kumar; Babu, Sukumaran Santhosh; Lahiri, Mayurika; Hazra, Partha (Chemical Communications, 2025)
In this study, we investigated the aggregation-induced delayed fluorescence (AIDF) properties of three luminogens - TN, TA, and TP. Our comprehensive theoretical analysis reveals a significant reduction in the Delta EST in their aggregated or solid-state, activating TADF, on a similar to mu s time-scale. Additionally, these luminogens demonstrate two-photon excited anti-Stokes photoluminescence emission and improved photocurrent generation, attributed to their strong charge transfer characteristics and longer singlet exciton lifetimes.

Steric hindrance modulated efficient thermally activated delayed fluorescence with non-linear optical, ferroelectric and piezoelectric properties - Dutta, Madhusudan; Chatterjee, Abhijit; Deka, Nilotpal; Tanwar, Riteeka; Mishra, Vishnu; Saha, Arindam; Mandal, Pankaj; Boomishankar, Ramamoorthy; Hazra, Partha (Chemical Science, 2025)
Multi-carbazole-based benzonitrile systems are efficient thermally activated delayed fluorescence (TADF) materials for organic light-emitting diodes (OLEDs). However, they suffer from low PLQY due to the large dihedral angle arising from steric crowding. Addressing this challenge, we demonstrate a potent strategy to engineer steric crowding in this work. To achieve our goal, we have designed three luminogens, namely, CzPHCN, tCzPHCN and Cz2CzPHCN based on phenanthrene-9,10-dicarbonitrile (PHCN), as an acceptor core to minimize the steric hindrance between the donor groups. Among the three luminogens, tCzPHCN exhibits a maximum PLQY of 86% and the highest RISC rate of 3.5 x 105 s-1, the underlying cause being the least dihedral angle of 45.72 degrees and suppressed intermolecular interaction due to the presence of the bulky tert-butyl group. Interestingly, our QM/MM calculations and experimental evidence suggest that the RISC process of both CzPHCN and tCzPHCN takes place via a hot exciton channel. Unlocking a new realm of applications, the unique non-centrosymmetric space group (Cmc21) of CzPHCN offers excellent SHG with a chi(2) value of 0.21 pm V-1 at 1320 nm. In addition to this, the molecule depicts good ferroelectric (PS = 0.32 mu C cm-2), piezoelectric energy harvesting (VOC = 2.8 V) and two-photon absorption properties.